Competitive relationships between sugar beet and weeds in dependence on time of weed control - M. Jursík; J. Holec; J. Soukup; V. Venclová (Plant, Soil and Environment, 2008)
Small plot trials were carried out in years 2001-2003 with sugar beet. In the treatment without weed control, dry weight of sugar beet top and LAI of sugar beet were very low (approx. 50 g/m2 and 0.5 m2/m2, respectively). Yield loss of sugar beet was 80-93%. Dominant weeds were Chenopodium album, Fumaria officinalis and Galium aparine. In the treatments where weeds were removed (by hand) until 4 leaf stage of sugar beet, dry weight of sugar beet top and LAI of sugar beet at first increased normally, but were markedly decreased from the half of the vegetation period. Yield loss of sugar beet was 54-28%. Dominant weed in this treatment was Amaranthus retroflexus. The development of sugar beet top dry weight and LAI of sugar beet was practically identical in the treatments where weeds were removed until 8-10 leaf stage of the crop and in those where weeds were removed during the whole vegetation period (500-900 g/m2, or 4-7 m2/m2, respectively). No yield loss of sugar beet was recorded. Dry weight of weeds did not exceed 30 g/m2 and LAI 0.1 m2/m2. A. retroflexus and Mercurialis annua were the most frequent weeds in this treatment.